Functional current collector for sodium-ion battery and preparation method and application thereof
Patent Information
- Application Number
- CN202611178550.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
该技术方案中底涂层侧重于粘结性能的提升,未能有效解决硬碳负极界面副反应及SEI膜不稳定等问题
本申请在功能集流体的底涂层中引入了复合功能添加剂用于提升钠离子电池中硬碳负极的循环性能,其中含氟小分子化合物在循环过程中原位构建富含NaF的致密稳定的SEI膜,NaF具有优异的机械强度和离子导电性,可有效抑制钠枝晶生长和电解液分解,减少活性钠和电解液的消耗;含极性官能团的聚合物凭借其极性官能团与集流体基材、硬碳颗粒形成强配位键,显著提升底涂层与集流体基材和负极活性层的界面结合力,有效防止循环过程中极片剥落、掉粉;Sn基修饰剂则提供充足的亲钠位点,能够降低钠离子成核过电位,促进钠离子均匀沉积,同时其自身的储钠活性可缓冲硬碳的体积膨胀,保护界面完整性。因此,含氟小分子化合物、含极性官能团的聚合物和Sn基修饰剂通过协同作用,可显著提升钠离子电池的循环性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery materials technology, specifically relating to a functional current collector for sodium-ion batteries, its preparation method, and its application. Background Technology
[0002] Sodium-ion batteries have broad application prospects in large-scale energy storage and portable electronic devices due to the abundant sodium resources, low cost, and environmental friendliness. Hard carbon materials, with their high sodium storage capacity and simple preparation process, are among the most industrially promising active materials for sodium-ion battery anodes.
[0003] However, hard carbon anodes still suffer from numerous problems during charge-discharge cycling, severely limiting their cycle performance improvement. Therefore, researchers are exploring various approaches to improve their cycle performance, with limited success. For example, patent CN118039859A discloses an anode sheet, its preparation method, and a sodium-ion battery, comprising: a modified anode active material, including a polydopamine-coated anode active material; an anode current collector, including a current collector with a base coating; an anode sheet, including the modified anode active material or the anode current collector; and a sodium-ion battery, including the modified anode active material, the anode current collector, or the anode sheet. In this technical solution, the base coating focuses on improving adhesion performance but fails to effectively address issues such as interfacial side reactions and SEI film instability in hard carbon anodes. Furthermore, this technical solution does not optimize the electron transport efficiency at the current collector interface, thus having a limited effect on improving the cycle life of hard carbon anodes.
[0004] Therefore, improving the cycle performance of hard carbon anodes in sodium-ion batteries is a technical challenge that urgently needs to be addressed. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this application aims to provide a functional current collector for sodium-ion batteries, its preparation method, and its application. This application introduces a composite functional additive into the undercoat of the functional current collector to improve the cycle performance of the hard carbon anode in sodium-ion batteries. The fluorine-containing small molecule compound constructs a dense and stable SEI film rich in NaF during cycling. NaF possesses excellent mechanical strength and ionic conductivity, effectively inhibiting sodium dendrite growth and electrolyte decomposition, reducing the consumption of active sodium and electrolyte. The polymer containing polar functional groups forms strong coordination bonds with the current collector substrate and hard carbon particles, significantly improving the interfacial adhesion between the undercoat, the current collector substrate, and the anode active layer, effectively preventing electrode peeling and powder shedding during cycling. The Sn-based modifier provides sufficient sodium-affinity sites, reducing the sodium ion nucleation overpotential and promoting uniform sodium ion deposition. Simultaneously, its own sodium storage activity buffers the volume expansion of hard carbon, protecting interfacial integrity. Therefore, fluorine-containing small molecule compounds, polymers containing polar functional groups, and Sn-based modifiers can significantly improve the cycle performance of sodium-ion batteries through synergistic effects.
[0006] To achieve the purpose of this application, the following technical solution is adopted: In a first aspect, this application provides a functional current collector for sodium-ion batteries, the functional current collector comprising: Current collector substrate.
[0007] A base coating is disposed on at least one side surface of the current collector substrate; the base coating includes an adhesive, a conductive agent, and a composite functional additive.
[0008] The composite functional additives include fluorinated small molecule compounds, polymers containing polar functional groups, and Sn-based modifiers.
[0009] This application introduces a composite functional additive into the undercoat of a functional current collector to improve the cycle performance of the hard carbon anode in sodium-ion batteries. The fluorine-containing small molecule compound constructs a dense and stable SEI film rich in NaF during cycling. NaF possesses excellent mechanical strength and ionic conductivity, effectively inhibiting sodium dendrite growth and electrolyte decomposition, reducing the consumption of active sodium and electrolyte. The polymer containing polar functional groups forms strong coordination bonds with the current collector substrate and hard carbon particles, significantly improving the interfacial adhesion between the undercoat, current collector substrate, and anode active layer, effectively preventing electrode peeling and powder shedding during cycling. The Sn-based modifier provides ample sodium-affinity sites, reducing the sodium ion nucleation overpotential and promoting uniform sodium ion deposition. Simultaneously, its sodium storage activity buffers the volume expansion of hard carbon, protecting interfacial integrity. Therefore, the fluorine-containing small molecule compound, the polymer containing polar functional groups, and the Sn-based modifier work synergistically to significantly improve the cycle performance of sodium-ion batteries.
[0010] In some embodiments, the mass content of the composite functional additive is 30-45% based on the total mass of the base coating, for example, it can be 30%, 35%, 40% or 45%.
[0011] This application introduces an appropriate amount of composite functional additives into the primer layer, which can ensure that the primer layer can fully exert its functions of interface stabilization, bonding enhancement and sodium-affinity deposition regulation. It avoids the situation where the amount of additive is too high, which would lead to a decrease in the internal conductivity and an increase in the internal resistance of the primer layer, or the modification effect is insufficient when the amount is too low, thus failing to achieve effective regulation of the SEI film and a significant improvement in the interface bonding.
[0012] In some embodiments, the mass ratio of the adhesive, conductive agent, and composite functional additive is (4-6):(49-66):(30-45), wherein the adhesive selection range "4-6" can be, for example, 4, 4.5, 5, 5.5, or 6, the conductive agent selection range "49-66" can be, for example, 49, 50, 55, 60, 65, or 66, and the composite functional additive selection range "30-45" can be, for example, 30, 35, 40, or 45.
[0013] In some embodiments, the mass ratio of the fluorinated small molecule compound, the polymer containing polar functional groups, and the Sn-based modifier is (0.9-1.1):(9-11):(25-30), wherein the fluorinated small molecule compound is selected in the range of "0.9-1.1", for example, 0.9, 1, or 1.1; the polymer containing polar functional groups is selected in the range of "9-11", for example, 9, 10, or 11; and the Sn-based modifier is selected in the range of "25-30", for example, 25, 26, 27, 28, 29, or 30.
[0014] In this application, the mass ratio of fluorinated small molecule compounds, polymers containing polar functional groups, and Sn-based modifiers in the composite functional additives introduced into the base coating is within a suitable range, which is conducive to the full synergistic effect of the three, complementing each other's functions and enhancing synergistic efficiency, achieving the technical effect of "1+1+1>3", and significantly improving the cycle stability of hard carbon anodes.
[0015] In some embodiments, the fluorinated small molecule compound includes any one or a combination of at least two of tetraethylammonium fluoride, tetrabutylammonium fluoride, or fluoroethylene carbonate.
[0016] In some embodiments, the polar functional groups include phenolic hydroxyl groups and / or amino groups.
[0017] In some embodiments, the polymer containing polar functional groups includes any one or a combination of at least two of polydopamine, polyethylene glycol, or polyvinyl alcohol.
[0018] In some embodiments, the Sn-based modifier includes any one or a combination of at least two of tin dioxide, sodium stannate, or elemental tin.
[0019] In some embodiments, the adhesive comprises any one or a combination of at least two of polyvinylidene fluoride, polyacrylic acid, or styrene-butadiene rubber.
[0020] In some embodiments, the conductive agent includes any one or a combination of at least two of acetylene black, Ketjen black, or carbon nanotubes.
[0021] In some embodiments, the current collector substrate is a metal foil. For example, it could be copper foil.
[0022] In some embodiments, the thickness of the base coating layer on one side is 0.5-5 μm, for example, it can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0023] In this application, an appropriate thickness of the base coating helps ensure that the composite functional additives are fully dispersed in the base coating and exert their effects on interfacial film formation, adhesion enhancement, and sodium-affinity deposition regulation.
[0024] Secondly, this application provides a method for preparing a functional current collector for sodium-ion batteries as described in the first aspect, the method comprising the following steps: A primer slurry is prepared; the primer slurry includes a binder, a conductive agent, a composite functional additive, and a solvent, wherein the composite functional additive includes a fluorinated small molecule compound, a polymer containing a polar functional group, and a Sn-based modifier.
[0025] The primer slurry is coated on at least one side of the current collector, and after drying, the functional current collector for sodium-ion batteries is obtained.
[0026] For example, the solvent may be N-methylpyrrolidone, etc.
[0027] In some embodiments, the preparation step of the primer slurry includes: The binder, conductive agent and solvent are mixed to obtain a premixed slurry.
[0028] The premixed slurry, the polymer containing polar functional groups, and the Sn-based modifier are mixed, and then a fluorine-containing small molecule compound is added to obtain the primer slurry.
[0029] The preparation of the primer slurry using the above-described steps facilitates the adsorption of polymers containing polar functional groups onto the surface of conductive agents and Sn-based modifier particles. The use of polar groups such as phenolic hydroxyl and amino groups to construct a stable dispersion network inhibits the aggregation of Sn-based modifiers and conductive agents. Finally, the introduction of fluorine-containing small molecule compounds prevents them from being prematurely coated and thus unable to exert their function. This homogenization method effectively ensures the uniform distribution of functional materials in the coating, fully leveraging their synergistic effect.
[0030] In some embodiments, the solid content of the primer slurry is 10-20%, for example, it can be 10%, 12%, 14%, 16%, 18% or 20%, etc.
[0031] In some embodiments, the mass content of the fluorinated small molecule compound is 0.9-1.1% based on the total solid mass of the primer slurry, for example, it can be 0.9%, 1% or 1.1%.
[0032] In some embodiments, the mass content of the polymer containing polar functional groups is 9-11% based on the total solid mass of the primer slurry, for example, it can be 9%, 10% or 11%.
[0033] In some embodiments, the Sn-based modifier has a mass content of 25-30% based on the total solid mass of the primer slurry, for example, it can be 25%, 26%, 27%, 28%, 29% or 30%.
[0034] In some embodiments, the preparation method includes the following steps: (1) Preparation of primer slurry: Under stirring conditions, the binder and organic solvent are mixed, and then a conductive agent is added to obtain a premixed slurry.
[0035] Under stirring conditions, the premixed slurry, the polymer containing polar functional groups, and the Sn-based modifier are mixed, and then a fluorine-containing small molecule compound is added to obtain the primer slurry with a solid content of 10-20%.
[0036] Based on the total solid mass of the primer slurry, the mass content of the fluorinated small molecule compound is 0.9-1.1%, the mass content of the polymer containing polar functional groups is 9-11%, and the mass content of the Sn-based modifier is 25-30%.
[0037] (2) Using a slot coating method, the primer slurry is coated on at least one surface of the metal foil at a coating speed of 25-35 m / min (e.g., 25 m / min, 27.5 m / min, 30 m / min, 32.5 m / min, or 35 m / min, etc.), and the surface density of the single-sided coating is 1.5-2.5 g / m².2 (For example, it could be 1.5g / m 2 1.75g / m 2 2g / m 2 2.25g / m 2 Or 2.5g / m 2 Then, it is dried at 100-150℃ (e.g., 100℃, 110℃, 120℃, 130℃, 140℃ or 150℃) to form a base coating with a thickness of 0.5-5μm, thus obtaining a functional current collector for sodium-ion batteries.
[0038] Thirdly, this application provides a negative electrode sheet, which includes a negative current collector and a negative active layer disposed on at least one side surface of the negative current collector.
[0039] Wherein, the negative electrode current collector is the functional current collector for sodium-ion batteries described in the first aspect; in the negative electrode active layer, the negative electrode active material includes hard carbon material.
[0040] Fourthly, this application provides a sodium-ion battery, the sodium-ion battery comprising the negative electrode sheet as described in the third aspect.
[0041] The numerical range described in this application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0042] Compared with the prior art, this application has the following advantages: This application introduces a composite functional additive into the undercoat of a functional current collector to improve the cycle performance of the hard carbon anode in sodium-ion batteries. The fluorine-containing small molecule compound constructs a dense and stable SEI film rich in NaF during cycling. NaF possesses excellent mechanical strength and ionic conductivity, effectively inhibiting sodium dendrite growth and electrolyte decomposition, reducing the consumption of active sodium and electrolyte. The polymer containing polar functional groups forms strong coordination bonds with the current collector substrate and hard carbon particles, significantly improving the interfacial adhesion between the undercoat, current collector substrate, and anode active layer, effectively preventing electrode peeling and powder shedding during cycling. The Sn-based modifier provides ample sodium-affinity sites, reducing the sodium ion nucleation overpotential and promoting uniform sodium ion deposition. Simultaneously, its sodium storage activity buffers the volume expansion of hard carbon, protecting interfacial integrity. Therefore, the fluorine-containing small molecule compound, the polymer containing polar functional groups, and the Sn-based modifier work synergistically to significantly improve the cycle performance of sodium-ion batteries. Detailed Implementation
[0043] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0044] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0045] In this application, "at least two combinations" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or at least two combinations" means any one of the listed items, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this application. In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this application, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0046] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments that do not conflict with existing technologies. The ordinal numbers "first," "second," "third," and "fourth," etc., used in this application in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0047] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0048] Example 1 This embodiment provides a functional current collector for sodium-ion batteries, the functional current collector comprising: Copper foil, 6μm thick.
[0049] A base coating is disposed on both sides of the copper foil; the base coating includes polyvinylidene fluoride, acetylene black and composite functional additives; the thickness of the base coating on one side is 2.5 μm.
[0050] The composite functional additive includes tetraethylammonium fluoride, polydopamine, and tin dioxide; based on the total mass of the base coating, the mass content of the composite functional additive is 38%; the mass ratio of polyvinylidene fluoride, acetylene black, and the composite functional additive is 5:57:38; and the mass ratio of tetraethylammonium fluoride, polydopamine, and tin dioxide is 1:10:27.
[0051] This embodiment also provides a method for preparing the above-mentioned functional current collector for sodium-ion batteries, the method comprising the following steps: (1) Preparation of primer slurry: Under stirring conditions, polyvinylidene fluoride and N-methylpyrrolidone were mixed, and then acetylene black was added to obtain a premixed slurry.
[0052] Under stirring conditions, the premixed slurry, polydopamine, and tin dioxide are mixed, and then tetraethylammonium fluoride is added to obtain the primer slurry with a solid content of 15%.
[0053] Specifically, based on the total solid mass of the primer slurry, the mass content of tetraethylammonium fluoride is 1%, the mass content of polydopamine is 10%, and the mass content of tin dioxide is 27%.
[0054] (2) The primer slurry is applied to both sides of the copper foil using a slot coating method at a coating speed of 30 m / min and a single-sided coating density of 2 g / m². 2 Then, it is dried at 125°C to form a base coating with a thickness of 2.5 μm, thus obtaining a functional current collector for sodium-ion batteries.
[0055] This embodiment also provides a negative electrode sheet, which includes a functional current collector for sodium-ion batteries as described above, and a negative electrode active layer disposed on one side surface of the functional current collector.
[0056] The negative electrode active layer comprises hard carbon material, conductive carbon black, and acrylonitrile multi-polymer waterborne binder (LA133) in a mass ratio of 8:1:1.
[0057] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, the method comprising the following steps: Hard carbon material, conductive carbon black, and acrylonitrile multi-polymer aqueous binder (LA133) were dispersed in an aqueous solvent and dispersed evenly to obtain a negative electrode slurry.
[0058] The negative electrode slurry is coated onto the surface of the base coating of the functional current collector, and then dried in a vacuum drying oven at 90°C for 1 hour to obtain the negative electrode sheet.
[0059] Example 2 This embodiment provides a functional current collector for sodium-ion batteries, the functional current collector comprising: Copper foil, 6μm thick.
[0060] A base coating is disposed on both sides of the copper foil; the base coating includes polyacrylic acid, Ketjen black and composite functional additives; the thickness of the base coating on one side is 1 μm.
[0061] The composite functional additive includes tetrabutylammonium fluoride, polydopamine, and tin dioxide; based on the total mass of the base coating, the mass content of the composite functional additive is 34.9%; the mass ratio of polyacrylic acid, Ketjen black, and the composite functional additive is 6:59.1:34.9; and the mass ratio of tetrabutylammonium fluoride, polydopamine, and tin dioxide is 0.9:9:25.
[0062] This embodiment also provides a method for preparing the above-mentioned functional current collector for sodium-ion batteries, the method comprising the following steps: (1) Preparation of primer slurry: Under stirring conditions, polyacrylic acid and N-methylpyrrolidone were mixed, and then Ketjen black was added to obtain a premixed slurry.
[0063] Under stirring conditions, the premixed slurry, polydopamine, and tin dioxide are mixed, and then tetrabutylammonium fluoride is added to obtain the primer slurry with a solid content of 10%.
[0064] Based on the total solid mass of the primer slurry, the mass content of the tetrabutylammonium fluoride is 0.9%, the mass content of the polydopamine is 9%, and the mass content of the tin dioxide is 25%.
[0065] (2) The primer slurry is applied to both sides of the copper foil using a slot coating method at a coating speed of 25 m / min and a single-sided coating density of 1.5 g / m². 2 Then, it is dried at 100°C to form a base coating with a thickness of 1μm, thus obtaining a functional current collector for sodium-ion batteries.
[0066] This embodiment also provides a negative electrode sheet, which includes a functional current collector for sodium-ion batteries as described above, and a negative electrode active layer disposed on one side surface of the functional current collector.
[0067] The negative electrode active layer comprises hard carbon material, conductive carbon black, and acrylonitrile multi-polymer waterborne binder (LA133) in a mass ratio of 8:1:1.
[0068] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, the method comprising the following steps: Hard carbon material, conductive carbon black, and acrylonitrile multi-polymer aqueous binder (LA133) were dispersed in an aqueous solvent and dispersed evenly to obtain a negative electrode slurry.
[0069] The negative electrode slurry is coated onto the surface of the base coating of the functional current collector, and then dried in a vacuum drying oven at 90°C for 1 hour to obtain the negative electrode sheet.
[0070] Example 3 This embodiment provides a functional current collector for sodium-ion batteries, the functional current collector comprising: Copper foil, 6μm thick.
[0071] A base coating is disposed on both sides of the copper foil; the base coating includes styrene-butadiene rubber, carbon nanotubes and composite functional additives; the thickness of the base coating on one side is 5 μm.
[0072] The composite functional additive includes fluoroethylene carbonate, polydopamine, and tin dioxide; based on the total mass of the base coating, the mass content of the composite functional additive is 42.1%; the mass ratio of styrene-butadiene rubber, carbon nanotubes, and the composite functional additive is 4:53.9:42.1; and the mass ratio of fluoroethylene carbonate, polydopamine, and tin dioxide is 1.1:11:30.
[0073] This embodiment also provides a method for preparing the above-mentioned functional current collector for sodium-ion batteries, the method comprising the following steps: (1) Preparation of primer slurry: Styrene-butadiene rubber and N-methylpyrrolidone were mixed under stirring conditions, and then carbon nanotubes were added to obtain a premixed slurry.
[0074] Under stirring conditions, the premixed slurry, polydopamine, and tin dioxide are mixed, and then ethylene fluorocarbonate is added to obtain the primer slurry with a solid content of 20%.
[0075] Based on the total solid mass of the primer slurry, the mass content of fluoroethylene carbonate is 1.1%, the mass content of polydopamine is 11%, and the mass content of tin dioxide is 30%.
[0076] (2) The primer slurry is applied to both sides of the copper foil using a slot coating method at a coating speed of 35 m / min and a single-sided coating density of 2.5 g / m². 2 Then, it is dried at 150°C to form a base coating with a thickness of 5μm, thus obtaining a functional current collector for sodium-ion batteries.
[0077] This embodiment also provides a negative electrode sheet, which includes a functional current collector for sodium-ion batteries as described above, and a negative electrode active layer disposed on one side surface of the functional current collector.
[0078] The negative electrode active layer comprises hard carbon material, conductive carbon black, and acrylonitrile multi-polymer waterborne binder (LA133) in a mass ratio of 8:1:1.
[0079] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, the method comprising the following steps: Hard carbon material, conductive carbon black, and acrylonitrile multi-polymer aqueous binder (LA133) were dispersed in an aqueous solvent and dispersed evenly to obtain a negative electrode slurry.
[0080] The negative electrode slurry is coated onto the surface of the base coating of the functional current collector, and then dried in a vacuum drying oven at 90°C for 1 hour to obtain the negative electrode sheet.
[0081] Example 4 The difference between this embodiment and Embodiment 1 is that the amount of tetraethyl ammonium fluoride added in step (1) is adjusted so that the mass content of tetraethyl ammonium fluoride is 0.8% based on the total solid mass of the primer slurry.
[0082] The remaining preparation methods and parameters are consistent with those in Example 1.
[0083] Example 5 The difference between this embodiment and Embodiment 1 is that the amount of tetraethyl ammonium fluoride added in step (1) is adjusted so that the mass content of tetraethyl ammonium fluoride is 1.2% based on the total solid mass of the primer slurry.
[0084] The remaining preparation methods and parameters are consistent with those in Example 1.
[0085] Example 6 The difference between this embodiment and embodiment 1 is that the amount of polydopamine added in step (1) is adjusted so that the mass content of polydopamine is 8% based on the total solid mass of the primer slurry.
[0086] The remaining preparation methods and parameters are consistent with those in Example 1.
[0087] Example 7 The difference between this embodiment and embodiment 1 is that the amount of polydopamine added in step (1) is adjusted so that the mass content of polydopamine is 12% based on the total solid mass of the primer slurry.
[0088] The remaining preparation methods and parameters are consistent with those in Example 1.
[0089] Example 8 The difference between this embodiment and embodiment 1 is that the amount of tin dioxide added in step (1) is adjusted so that the mass content of tin dioxide is 17% based on the total solid mass of the primer slurry.
[0090] The remaining preparation methods and parameters are consistent with those in Example 1.
[0091] Example 9 The difference between this embodiment and embodiment 1 is that the amount of tin dioxide added in step (1) is adjusted so that the mass content of tin dioxide is 22% based on the total solid mass of the primer slurry.
[0092] The remaining preparation methods and parameters are consistent with those in Example 1.
[0093] Example 10 The difference between this embodiment and embodiment 1 is that the amount of tin dioxide added in step (1) is adjusted so that the mass content of tin dioxide is 32% based on the total solid mass of the primer slurry.
[0094] The remaining preparation methods and parameters are consistent with those in Example 1.
[0095] Example 11 The difference between this embodiment and embodiment 1 is that the amount of tin dioxide added in step (1) is adjusted so that the mass content of tin dioxide is 37% based on the total solid mass of the primer slurry.
[0096] The remaining preparation methods and parameters are consistent with those in Example 1.
[0097] Example 12 The difference between this embodiment and Embodiment 1 is that the amount of composite functional additive added is adjusted so that, based on the total mass of the base coating, the mass content of the composite functional additive is 25%.
[0098] The remaining preparation methods and parameters are consistent with those in Example 1.
[0099] Example 13 The difference between this embodiment and Embodiment 1 is that the amount of composite functional additive added is adjusted so that, based on the total mass of the base coating, the mass content of the composite functional additive is 50%.
[0100] The remaining preparation methods and parameters are consistent with those in Example 1.
[0101] Example 14 The difference between this embodiment and Embodiment 1 is that the amount of tin dioxide added is adjusted so that the mass ratio of tetraethylammonium fluoride to tin dioxide is 1:35.
[0102] The remaining preparation methods and parameters are consistent with those in Example 1.
[0103] Example 15 The difference between this embodiment and Embodiment 1 is that the amount of tin dioxide added is adjusted so that the mass ratio of tetraethylammonium fluoride to tin dioxide is 1:20.
[0104] The remaining preparation methods and parameters are consistent with those in Example 1.
[0105] Comparative Example 1 The difference between this comparative example and Example 1 is that the composite functional additive does not contain fluorinated ethylene carbonate.
[0106] The remaining preparation methods and parameters are consistent with those in Example 1.
[0107] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite functional additive does not contain polydopamine.
[0108] The remaining preparation methods and parameters are consistent with those in Example 1.
[0109] Comparative Example 3 The difference between this comparative example and Example 1 is that the composite functional additive does not contain tin dioxide.
[0110] The remaining preparation methods and parameters are consistent with those in Example 1.
[0111] Comparative Example 4 The difference between this comparative example and Example 1 is that the base coating does not contain composite functional additives.
[0112] The remaining preparation methods and parameters are consistent with those in Example 1.
[0113] Comparative Example 5 The difference between this comparative example and Example 1 is that no base coating is applied.
[0114] The remaining preparation methods and parameters are consistent with those in Example 1.
[0115] Performance testing A sodium-ion battery is fabricated based on the negative electrode sheet provided in the above embodiments and comparative examples. The fabrication steps include: The CR2032 button cell battery casing and a 20μm thick glass fiber separator are selected. In an argon-filled glove box, the negative electrode casing, negative electrode plate, electrolyte, separator, electrolyte, sodium plate, gasket, spring sheet, and positive electrode casing are assembled in sequence. After assembly, the casing is sealed and pressed to obtain the CR2032 button cell battery.
[0116] The CR2032 button cell battery underwent cycle performance testing, and the test steps included: The CT3002A button battery charge-discharge tester was used to conduct constant current charge-discharge cycle tests at a rate of 0.2C in an environment of 25±2℃ with a voltage window of 0.01-2V. The charge-discharge specific capacity and capacity retention rate were recorded at the 10th, 50th, and 100th cycles to evaluate its cycle stability.
[0117] The test results are shown in Table 1.
[0118] Table 1 analyze: As shown in Table 1, this application improves the cycling performance of the hard carbon anode by applying a base coating to the current collector substrate. In addition to binders and conductive agents, the base coating also incorporates fluorine-containing small molecule compounds, polymers with polar functional groups, and Sn-based modifiers. The fluorine-containing small molecule compounds construct a dense and stable SEI film rich in NaF during cycling. NaF possesses excellent mechanical strength and ionic conductivity, effectively inhibiting sodium dendrite growth and electrolyte decomposition, thus reducing the consumption of active sodium and electrolyte. The polymers with polar functional groups form strong coordination bonds with the current collector substrate and hard carbon particles, significantly enhancing the interfacial bonding between the base coating, the current collector substrate, and the active layer of the anode, effectively preventing electrode peeling and powder shedding during cycling. The Sn-based modifier provides ample sodium-affinity sites, reducing the overpotential for sodium ion nucleation and promoting uniform sodium ion deposition. Simultaneously, its sodium storage activity buffers the volume expansion of the hard carbon, protecting the interfacial integrity. Therefore, fluorine-containing small molecule compounds, polymers containing polar functional groups, and Sn-based modifiers can significantly improve the cycle performance of sodium-ion batteries through synergistic effects.
[0119] As can be seen from the comparison between Example 1 and Examples 4-5, if the mass content of tetraethylammonium fluoride is too low, there will be insufficient fluorine source to participate in the construction of a stable SEI film, resulting in an increase in side reactions; if the mass content of tetraethylammonium fluoride is too high, it will cause the pores of the undercoat to be blocked, the conductivity to decrease, and the battery cycle performance to be reduced.
[0120] As can be seen from the comparison between Example 1 and Examples 6-7, if the mass content of polydopamine is too low, it is difficult to form a stable bond between the copper foil, the base coating and the hard carbon, and the coating is prone to peeling off; if the mass content of polydopamine is too high, it will significantly increase the viscosity of the slurry system, resulting in uneven slurry dispersion and local agglomeration, which will seriously aggravate the problem of ion transport difficulties after a long time.
[0121] As can be seen from the comparison between Example 1 and Examples 8-11, if the mass content of tin dioxide is too low, the sodium affinity of the current collector surface is insufficient, the sodium ion deposition is uneven, and the battery cycle polarization continues to increase; if the mass content of tin dioxide is too high, the inorganic materials are prone to agglomeration and sedimentation, resulting in uneven local conductive network of the bottom coating, which affects the long-term stability of the battery cycle performance.
[0122] As can be seen from the comparison between Example 1 and Examples 12-13, if the mass content of the composite functional additive is too low, the synergistic effect is insufficient, there are many interface defects, and it is impossible to effectively suppress side reactions and volume deformation; if the mass content of the composite functional additive is too high, the coating adhesion and conductivity will decrease, and phenomena such as powder shedding will occur, which is not conducive to the performance of the active material after long-term charge and discharge.
[0123] A comparison of Example 1 and Examples 14-15 shows that if the mass ratio of tetraethylammonium fluoride to tin dioxide is too small, although there are abundant sodium-loving deposition sites, a stable and dense SEI film cannot be formed, and interfacial side reactions continue to occur; if the mass ratio of tetraethylammonium fluoride to tin dioxide is too large, there are insufficient sodium-loving modification sites, the sodium ion deposition ability weakens, and polarization increases.
[0124] As can be seen from the comparison between Example 1 and Comparative Example 1, if the composite functional additive does not contain fluorinated ethylene carbonate, a highly stable and dense fluorinated SEI film cannot be formed at the interface, the interface impedance continues to increase, and the capacity decays severely.
[0125] As can be seen from the comparison between Example 1 and Comparative Example 2, if polydopamine is not present in the composite functional additive, the adhesion ability of the base coating to the substrate and the active layer will be greatly reduced, the active material will easily fall off during the cycle, and the capacity retention rate will be reduced.
[0126] As can be seen from the comparison between Example 1 and Comparative Example 3, if there is no tin dioxide in the composite functional additive, the uniformity of sodium ion transport and deposition is poor, and the electrode polarization phenomenon is severe.
[0127] As can be seen from the comparison between Example 1 and Comparative Example 4, if there are no composite functional additives in the base coating, the base coating only has basic conductivity, the negative electrode interface side reactions increase, the structural stability deteriorates, and the polarization growth is faster.
[0128] As can be seen from the comparison between Example 1 and Comparative Example 5, if no base coating is provided, the copper foil will be in direct contact with the negative electrode and electrolyte, and interface corrosion and side reactions will be easily aggravated during the cycle.
[0129] It should be noted that this application illustrates the process method through the above embodiments, but this application is not limited to the above process steps, that is, it does not mean that this application must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the raw materials used in this application, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.
Claims
1. A functional current collector for sodium-ion batteries, characterized in that, The functional current collector includes: Current collector substrate; A base coating is disposed on at least one surface of the current collector substrate; the base coating includes an adhesive, a conductive agent, and a composite functional additive. The composite functional additives include fluorinated small molecule compounds, polymers containing polar functional groups, and Sn-based modifiers.
2. The functional current collector for sodium-ion batteries according to claim 1, characterized in that, Based on the total mass of the base coating, the mass content of the composite functional additive is 30-45%; And / or, the mass ratio of the adhesive, conductive agent and composite functional additive is (4-6):(49-66):(30-45).
3. The functional current collector for sodium-ion batteries according to claim 1 or 2, characterized in that, The mass ratio of the fluorinated small molecule compound, the polymer containing polar functional groups, and the Sn-based modifier is (0.9-1.1):(9-11):(25-30).
4. The functional current collector for sodium-ion batteries according to any one of claims 1-3, characterized in that, The fluorinated small molecule compound includes any one or a combination of at least two of tetraethylammonium fluoride, tetrabutylammonium fluoride, or fluoroethylene carbonate. And / or, the polar functional groups include phenolic hydroxyl groups and / or amino groups; And / or, the polymer containing polar functional groups includes any one or a combination of at least two of polydopamine, polyethylene glycol, or polyvinyl alcohol; And / or, the Sn-based modifier includes any one or a combination of at least two of tin dioxide, sodium stannate, or elemental tin.
5. The functional current collector for sodium-ion batteries according to any one of claims 1-4, characterized in that, The adhesive includes any one or a combination of at least two of polyvinylidene fluoride, polyacrylic acid, or styrene-butadiene rubber. And / or, the conductive agent includes any one or a combination of at least two of acetylene black, Ketjen black, or carbon nanotubes; And / or, the current collector substrate is a metal foil; And / or, the thickness of the base coating on one side is 0.5-5 μm.
6. A method for preparing a functional current collector for sodium-ion batteries as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: A primer slurry is prepared; the primer slurry includes a binder, a conductive agent, a composite functional additive, and a solvent, wherein the composite functional additive includes a fluorinated small molecule compound, a polymer containing polar functional groups, and a Sn-based modifier; The primer slurry is coated on at least one side of the current collector, and after drying, the functional current collector for sodium-ion batteries is obtained.
7. The preparation method according to claim 6, characterized in that, The preparation steps of the primer slurry include: The binder, conductive agent and solvent are mixed to obtain a premixed slurry; The premixed slurry, the polymer containing polar functional groups, and the Sn-based modifier are mixed, and then a fluorine-containing small molecule compound is added to obtain the primer slurry. And / or, the solid content of the primer slurry is 10-20%; And / or, based on the total solids mass of the primer slurry, the mass content of the fluorinated small molecule compound is 0.9-1.1%; And / or, based on the total solids mass of the primer slurry, the mass content of the polymer containing polar functional groups is 9-11%; And / or, based on the total solid mass of the primer slurry, the mass content of the Sn-based modifier is 25-30%.
8. The preparation method according to claim 6 or 7, characterized in that, The preparation method includes the following steps: (1) Preparation of primer slurry: Under stirring conditions, the binder and organic solvent are mixed, and then a conductive agent is added to obtain a premixed slurry; Under stirring conditions, the premixed slurry, the polymer containing polar functional groups and the Sn-based modifier are mixed, and then a fluorine-containing small molecule compound is added to obtain the primer slurry with a solid content of 10-20%. Specifically, based on the total solid mass of the primer slurry, the mass content of the fluorinated small molecule compound is 0.9-1.1%, the mass content of the polymer containing polar functional groups is 9-11%, and the mass content of the Sn-based modifier is 25-30%. (2) Using a slot coating method, the primer slurry is coated on at least one side of the metal foil at a coating speed of 25-35 m / min, and the surface density of the single-sided coating is 1.5-2.5 g / m². 2 Then, it is dried at 100-150℃ to form a base coating with a thickness of 0.5-5μm, thus obtaining a functional current collector for sodium-ion batteries.
9. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector and a negative active layer disposed on at least one side surface of the negative current collector; Wherein, the negative electrode current collector is the functional current collector for sodium-ion batteries as described in any one of claims 1-5; in the negative electrode active layer, the negative electrode active material includes hard carbon material.
10. A sodium-ion battery, characterized in that, The sodium-ion battery includes the negative electrode as described in claim 9.